PENGARUH ECONOMIC VALUE ADDED, RESIDUAL INCOME, EARNINGS DAN ARUS KAS OPERASI TERHADAP RETURN YANG DITERIMA OLEH PEMEGANG SAHAM (Studi pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia) - Ananto, Niel; Pasuhuk, Lefrand (JBE (Journal of Business and Economics), 2013)
This study analyzed the influence of economic value added, residual income, and two mandated performance measures, earnings and cash flow from operations to the shareholders’ return of the public companies listed on Jakarta Stock Exchange. This study was also intended to know which performance measures have the most significant effect to the stockholders’ returns. This study used linier regression to see the contribution form each independent variables influenced stockholders’ return. The hypotheses was economic value added, residual income, earning and cash flow operation have significant influence to the stockholders’ return. The most significant effect was from cash flow operation regression. The next variable which has significant effect also was earning.